Gambaran Tingkat Kecemasan dan Kadar Hormon Kortisol Ibu Nifas: Anxiety and Cortisol Levels among Postpartum Mother's - Anggraeni, Ni Putu Dian Ayu; Saudia, Baiq Eka Putri (Poltekkes Kemenkes Palu, 2021)
Introduction: Physical, social, mental, and psychological issues are common in the first few days after giving birth. According to some research, postpartum depression symptoms are linked to high cortisol levels. Postpartum psychological stress causes higher cortisol levels. Objective: The aim of this study was to look at postpartum mother's anxiety and cortisol levels. Methods: An Analytical Survey with a Cross-Sectional Approach is used in this analysis. With simple random sampling, there were 38 samples that met the inclusion criteria. Data was collected using the PSAS questionnaire for anxiety and an ELISA test for cortisol levels. Univariate and Pearson correlation test is used in the data analysis. Results: The majority of postpartum mothers reported mild anxiety in the first 24 hours after childbirth, with an average cortisol level of 10.034ng/ml 47.4%. The average level of the puerperal hormone cortisol in primiparous women was 14.60ng/ml higher than in multiparous women 7.42 ng/dl. Conclusion: With a p-value of 0.017, there was a substantial difference in cortisol levels between primiparous and multiparous postpartum mothers. With a p-value <0.001, there was a close connection between anxiety scores and cortisol levels. Future studies would need to focus on making it easier for postpartum mothers to feel less anxious.